LOW LEVEL LIGHT THERAPY FOR THE TREATMENT OF RECALCITRANT CHALAZIA (The Research of Medical Science Review, 2024)
To determine efficacy of low level light therapy for the treatment of recalcitrant chalazion, Quasi-experimental study, Military Hospital, Rawalpindi from January to July 2023, 150 patients who had recalcitrant chalazion were included in the study. Baseline demographics were documented. All patients were treated with low level light therapy and efficacy was determined in terms of frequency of resolution of chalazion. Data was analyzed by SPSS 20.00, Mean age of patients was 31.39 ± 8.51 years. There were 81 (54.00%) male and 69 (46.00%) female patients. Mean duration of chalazia was 6.45 ± 1.12 weeks. Mean duration of being admitted at the hospital was 13.22 ± 5.31 days. Left eye was involved in 71 (47.33%), right eye in 55 (36.67%) and both eyes were affected in 24 (16.00%) patients. 101 (67.33%) were smokers. Frequency of patients in which complete resolution was achieved was 116 (77.33%) while 34 (22.67%) patients still had chalazion persisting after therapy, Low level light therapy is an efficacious therapy for management of recalcitrant chalazion with a resolution rate of 77.33%.